PENGARUH LUAS BIDANG REKATAN LAPIS GFRP TERHADAP KAPASITAS LENTUR BALOK BETON BERTULANG - Rai Widiarsa, Ida Bagus; Deskarta, Putu (Jurnal Ilmiah Teknik Sipil, 2012)
Debonding of GFRP plate from the surface of concrete results the capacity of strenghtened reinforced concrete beams becomes not optimal. To obtain the optimal flexural capacity and avoiding the debonding of GFRP plate from concrete surface, therefore it is important to know the influence of bonding area between GFRP plate and concrete surface. Samples that were used in this research were concrete cylinders with diameter of 15 cm and height of 30 cm, and concrete beams with the size of 10 cm x 14 x cm 140 cm. Beams reinforcement consist of flexural reinforcement of 2Ø10 mm and shear reinforcement of Ø6 mm with space of 60 mm. The samples were made in 4 types that were beam without addition of GFRP sheet; beam with addition of 2 sheets of GFRP plate and 100% addition of bonding area of GFRP; beam with addition of 2 sheets of GFRP plate and 200% addition of bonding area of GFRP; and beam with addition of 2 sheets of GFRP plate and 200% addition of bonding area of GFRP with side folding. The GFRP plates that were used in this research consist of glass fiber which in form of woven roving glued to the beams by epoxy resin. The data that were observed such as beams failure model, maximum load and deflection. The results of this research show that the addition of bonding area of GFRP improved the flexural capacity of reinforced concrete beam. The addition of 100%, 200% and 200% with side folding of bonding area of GFRP plate increased the maximum moment of beams by 14%, 21,39% and 14%, respectively. On the other hand it did not work optimally due to the debonding between GFRP plate and beam. The average bonding strength of GFRP plate on the beams was 1,453 MPa which was 1/5 of the required bonding strength of GFRP plate
Keywords: bonding area, flexural capacity, reinforced concrete beam